Endourologic Management of Upper Tract Transitional Cell Carcinoma following Cystectomy and Urinary Diversion - Jeffrey John Tomaszewski; Marc Christopher Smaldone; Michael Cecil Ost (Advances in Urology)
Traditionally, nephroureterectomy is the gold standard therapy for upper tract recurrence of transitional cell carcinoma (TCC) following cystectomy and urinary diversion. With advances in endoscopic equipment and improvements in technique, conservative endourologic management via a retrograde or antegrade approach is technically feasible with acceptable outcomes in patients with bilateral disease, solitary renal units, chronic renal insufficiency, or significant medical comorbidities. Contemporary studies have expanded the utility of these techniques to include low-grade, low-volume disease in patients with a normal contralateral kidney. The aim of this report is to review the current outcomes of conservative management for upper tract disease and discuss its application and relevance in patients following cystectomy with lower urinary tract reconstruction.